2011
DOI: 10.1017/s1461145711001490
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of OROS-MPH and atomoxetine on executive function improvement in ADHD: a randomized controlled trial

Abstract: This study aimed to compare the effects of osmotic release oral system-methylphenidate (OROS-MPH) and atomoxetine (ATX) on executive function in children and adolescents with attention deficit hyperactivity disorder (ADHD) by a randomized controlled trial. Subjects who met DSM-IV ADHD criteria were randomized to receive either OROS-MPH or ATX treatment. The doses were titrated to achieve optimal response and then maintained for 4-6 wk. A battery of executive function tests and the Behavior Rating Inventory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
58
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 79 publications
4
58
1
11
Order By: Relevance
“…Our results are consistent with many studies on neuropsychological evaluation and ADHD, showing an improvement in WM, IC, and MF, as well as a relevant medication effect on EF performance at various levels 11,13,15,27,28 . Other studies that also analyzed attention and EF, and the effects of methylphenidate treatment in children with ADHD, did not find similar results to ours, but most of them ADHD: attention-deficit/hyperactivity disorder; M: mean; SD: standard deviation; p: t-student probability statistical significance was set at the p < 0.05 level.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with many studies on neuropsychological evaluation and ADHD, showing an improvement in WM, IC, and MF, as well as a relevant medication effect on EF performance at various levels 11,13,15,27,28 . Other studies that also analyzed attention and EF, and the effects of methylphenidate treatment in children with ADHD, did not find similar results to ours, but most of them ADHD: attention-deficit/hyperactivity disorder; M: mean; SD: standard deviation; p: t-student probability statistical significance was set at the p < 0.05 level.…”
Section: Discussionsupporting
confidence: 92%
“…Normative data on typical children have shown adequate developmental progression, highlighting the differences between the first assessment and after methylphenidate in the children with ADHD. These results suggest that these measures provide an important tool to assess children at risk for ADHD showing deficits in attention areas and EF 11,13,15,27,28,31 . We used the WISC III digit span backward and arithmetic tests to evaluate WM abilities 19 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Another study was performed by our group. We found that rs3785143 in SLC6A2 had significant association with responder status, whereas rs2279805 was associated with remission status (Yang et al 2012). The former SNP was Robust response was defined as the decrease of ‡40% on the ADHD-RS-IV total score from baseline to the end of the trial.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, our result was consistent with Ramoz's. In the Yang et al (2012) study, we also reported a haplotype with two SNPs at ADRA2A (rs1800544 and rs553668) in association with nonremission of ADHD symptoms after atomoxetine treatment. There was no previous study investigating the association between DBH and atomoxetine response.…”
Section: Discussionmentioning
confidence: 74%